2016
DOI: 10.20886/jpth.2016.10.2.135-143
|View full text |Cite
|
Sign up to set email alerts
|

KARAKTERISTIK SERAT KAYU HIBRID Acacia auriculiformis x Acacia mangium SEBAGAI BAHAN BAKU PULP

Abstract: Acacia auriculiformis x Acacia mangium hybrid (Aa x Am) is a promising Acacia hybrid for pulp. Wood properties of the hybrid have been reported for their physical and chemical characteristics, but the fiber characteristics have not been investigated. This study was aimed to investigate the fiber characteristics of the hybrid. Wood samples were collected from three years old of Aa x Am hybrid trees planted in a hybrid seed orchard. For comparison, wood sample from other three species: A. mangium x A. auriculifo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
(4 reference statements)
0
6
0
Order By: Relevance
“…The fiber dimensions of the wood from the four Acacias as used in this study were previously reported and the value is presented at Table 2 [25]. Except for the fiber length, all fiber dimensions were significantly different (p<0.05) among the four Acacias.…”
Section: Fiber Dimensionsmentioning
confidence: 94%
See 3 more Smart Citations
“…The fiber dimensions of the wood from the four Acacias as used in this study were previously reported and the value is presented at Table 2 [25]. Except for the fiber length, all fiber dimensions were significantly different (p<0.05) among the four Acacias.…”
Section: Fiber Dimensionsmentioning
confidence: 94%
“…Although a direct comparison between these two studies is not appropriate because of the differences in the sites and stand, it revealed that the age likely affected the change of fiber dimension of Acacia species. [25] Remark: average numbers followed by the sane letters in a column were not significantly different at the level of Based on the fiber dimension properties as mentioned above, the four Acacias are classified as the short fiber tropical species (fiber length ≤ 0.900 mm). The value of fiber dimension is important to assess the suitability of the wood for the type of end-product, especially for pulp and paper.…”
Section: Fiber Dimensionsmentioning
confidence: 97%
See 2 more Smart Citations
“…The S. caseolaris branch has the highest Flexibility Ratio (FR) of 0.29 and the A. marina branch has the lowest 0.23. According to Sunarti et al [25] wood as a raw material with a lower Muhlstep number value will produce better pulp quality, the density of the pulp sheet produced will be better with better strength properties. A high coefficient of flexibility will have a thin wall thickness and easily deform so that it will produce pulp sheets with better strength.…”
Section: Fiber Qualitymentioning
confidence: 99%